Enseñanza de la derivada y el límite apoyada con TIC / Teaching and Learning of the Derivative and the Supported Limit with Digital Resources - Gutiérrez Mendoza, Lucia (Revista Internacional de Aprendizaje en Ciencia, Matemáticas y Tecnología, 2019)
ABSTRACT This research work, exploratory type, focuses on the teaching of the concept of the limit and the derivative, from didactic strategies supported by digital resources (Geogebra), in order to improve the teaching-learning processes and mathematical skills of students who take the subject of differential calculus. The practices were developed with engineering students from the Universidad Militar Nueva Granada; in the first part, limits and derivative exercises were developed in pencil and paper, and in a second part, Geogebra worked with the calculation of some limits following the given instructions. RESUMEN Este trabajo de investigación, de tipo exploratoria, se centra en la enseñanza del concepto del límite y la derivada, a partir de estrategias didácticas apoyadas con recursos digitales (Geogebra), con el fin de mejorar los procesos de enseñanza-aprendizaje y las competencias matemáticas de los estudiantes que cursan la asignatura de cálculo diferencial. Las prácticas se desarrollaron con estudiantes de ingeniería de la Universidad Militar Nueva Granada; en una primera parte se desarrollaron ejercicios de límites y derivadas a lápiz y papel, y en una segunda parte se trabajó con Geogebra el cálculo de algunos límites siguiendo las instrucciones dadas.